1996
DOI: 10.1089/jir.1996.16.695
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-Mediated Hyperalgesia/Allodynia and Increased Spinal IL-6 Expression in a Rat Mononeuropathy Model

Abstract: It has been suggested that neuroimmunologic mechanisms may be involved in the development and maintenance of neuropathic pain. To further address this concept, the immunoreactive spinal expression of the pro-inflammatory cytokine, interleukin-6 (IL-6), was determined in the mononeuropathy model in the rat, sciatic cryoneurolysis (SCN). This well-established animal model expresses behaviors suggestive of neuropathic pain in humans. Immunohistochemical localization in the spinal cord was determined at 3, 7, 14, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
212
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(231 citation statements)
references
References 29 publications
14
212
0
5
Order By: Relevance
“…It has been reported that IL-6 also interferes with pain sensation in rats; for instance, intracerebro-ventricular injection of IL-6 induces thermal hyperalgesia [15]. In line with this finding is the observation that intrathecal IL-6 production results in allodynia and thermal hyperalgesia following peripheral nerve injury [6]. The possible effects of IL-6 on nerve root are still unknown.…”
Section: Fibronectinmentioning
confidence: 84%
“…It has been reported that IL-6 also interferes with pain sensation in rats; for instance, intracerebro-ventricular injection of IL-6 induces thermal hyperalgesia [15]. In line with this finding is the observation that intrathecal IL-6 production results in allodynia and thermal hyperalgesia following peripheral nerve injury [6]. The possible effects of IL-6 on nerve root are still unknown.…”
Section: Fibronectinmentioning
confidence: 84%
“…The concentrations of neurofilament and nociceptin were increased in the experimental spinal nerve root injury group; however, there were no intergroup differences in glial fibrillary acidic protein, neuron-specific enolase, S-100, IL-8, or substance P endopeptidase activity. DeLeo et al [4] demonstrated that IL-6 was produced both locally and centrally in response to nerve damage. The elevated IL-6 levels in the patients with lumbar radiculopathy were ascribed to nerve damage rather than nucleus pulposus.…”
Section: Discussionmentioning
confidence: 99%
“…The highest possible JOA score-L is 29 points. The mean JOA score-L was 12.4 points (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. To evaluate the relationships between neurological deficits and the concentrations of the cytokines, the sum of motor disturbance and the sensory disturbance of JOA score-L (neurological deficits score) was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, spinal cord IL-6 has been implicated in other exaggerated pain states, such as allodynia induced by peripheral nerve injury (Arruda et al, 2000;DeLeo et al, 1996), sciatic inflammatory neuropathy (Chacur et al, 2004;Milligan et al, 2003), and intrathecal fractalkine . IL-6 has been suggested to be involved in nociception at the level of the skin, nerve, dorsal root ganglia (DRG), and spinal cord, and its expression is induced in response to nerve injury in spinal cord, DRG sensory neurons (Arruda et al, 1998;Lee et al, 2004;Murphy et al, 1995), and in peripheral nerves (Ma and Quirion, 2005;Okamoto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While IL-6 can act as a proinflammatory cytokine, under other circumstances it can act as an anti-inflammatory cytokine instead (Jordan et al, 1995;Tilg et al, 1997;Tilg et al, 1994). Given that IL-6 can exert diametrically opposing actions under different conditions, it is perhaps not surprising that both pain facilitatory and pain inhibitory effects of IL-6 have been reported (DeLeo et al, 1996;Flatters et al, 2003). We have recently documented that i.t.…”
Section: Introductionmentioning
confidence: 99%